Increasing the Knowledge of Gastrointestinal Disorder Related to Mental Health Issue in Supporting Sustainable Development Goals (SGDs) for Indonesia Immigrants in Zagreb, Croatia - Shabrina, Ayu (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Sustainable development goals (SDGs) involve civil society and other organizations. All health issues in the SDGs are integrated into one goal, such as ensuring a healthy life and promoting well-being for all people. The purpose of this community service is to increase the knowledge of Indonesian immigrants in Zagreb, Croatia, about gastrointestinal disorders related to mental health issues in order to achieve a healthy life. This community service started by analyzing the status of the immigrants' health in Zagreb under the coordination of Bjelovar University and public pharmacy in Bjelovar. This event was held at the Embassy of the Republic of Indonesia in Zagreb, Croatia. The event was continued by socialization about gastrointestinal disorders and the use of herbs and medicines. This event was attended by 35 participants aged 30 to 50 years old. The participants acknowledge the mental health issues that can cause various disorders, such as gastrointestinal disorders, diabetes mellitus and many more. Based on the event, it is known that more than 65% of participants understood about healthy lifestyle, the use of multivitamins and medicines, and also about the metabolic disorder. Overall, this activity increased participants' understanding of gastrointestinal disorders and mental health and promoted a healthy lifestyle.